ANALYSIS OF INVESTMENT AND INNOVATION ACTIVITY OF INDUSTRIAL ENTERPRISES OF UKRAINE - RATUSHNYAK, O.; LYALYUK, O. (Herald of Khmelnytskyi National University. Economic sciences, 2021)
The purpose of the article is to analyze the investment and innovation activities of Ukrainian industrial enterprises. The paper identifies the level of the world innovation activity of Ukraine in 2020 by the global innovation index. It should be noted, that the obtained results of the index are average, compared to countries around the world and higher than in neighbouring countries such as Russia and Belarus. The innovation activity and the number of Ukrainian industrial enterprises that have introduced innovations over the last ten years have been analyzed. The results of the analysis are reflected both in the number of industrial enterprises innovative activity and in percentage to the total number of industrial enterprises. The greatest innovative activity of industrial enterprises is mainly indicated in large cities with developed infrastructure. Innovative activity by types of economic activity for the last year is considered. The leader of such activity remains is the processing industry, which includes enterprises engaged in the production of food, beverages, chemicals, pharmaceuticals, drugs and others. The costs of innovations of industrial enterprises in monetary units, as well as in per cent to the total volume of sold industrial products and the total volume of sold innovative products are analyzed. The main sources of financing the innovative activity of industrial enterprises for the last ten years are considered, among which the main ones are the own funds of enterprises. External and internal factors influencing the innovation activity of industrial enterprises are considered. The key directions for increasing the innovative activity of industrial enterprises of Ukraine and attracting investment both at the state level and at the enterprise level are presented.